Typology of Corner Buildings in the District of Central Market Medan - Alifa Azzahra Nasution; Beny O Y Marpaung Marpaung; Hilma Tamiami Fachruddin (International Journal of Architecture and Urbanism, 2024)
The Central Market Medan is a district that holds significant architectural and historical value, especially in Medan. Built during the colonial era in 1929, the Central Market Medan was inaugurated in 1933 and consisted of 183 shopping buildings. The Central Market Medan played a role as a generator of commercial activity and was declared the largest market area in Medan during that period. As a commercial district, corner buildings play a significant role in optimizing commercial functions. Most of the corner buildings were built with special treatment that can be seen from the corner form and can be easily distinguished from the surrounding buildings to emphasize the presence of street corners. This research aims to analyze the corner buildings in Central Market Medan to find out the correlation between the corner building typology theory and corner buildings in Central Market Medan. The research is conducted using a qualitative method by field observations and literature studies. The results of this research are expected to find the typology of corner buildings in the District of Central Market Medan in the mean of emphasizing the corners in urban space. It is hoped that this research will contribute to developing architectural knowledge, especially regarding the corner buildings in the District of Central Market Medan.